PENGARUH MEKANISME CORPORATE GOVERNANCE, TIPE INDUSTRI, DAN KEPEMILIKAN PUBLIK PADA PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) - Okta Dewi, Ni Komang Sri Cristi; Sisdyani, Eka Ardhani (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.08.TAHUN.2022DO - 10.24843/EEB.2022.v11.i08.p03, 2022)
This study aims to determine the effect of corporate governance mechanisms, type of industry, and public ownership of companies on CSR disclosure through the sustainability reports of SOEs listed on the IDX for the 2017-2019 period. The population in this study were 26 state-owned companies. Determination of the number of samples using purposive sampling technique with 3 criteria so as to obtain 18 samples that meet the three criteria. The data analysis used is multiple linear analysis. The results of this study indicate that corporate governance mechanisms, type of industry, and company public ownership have a positive effect on CSR disclosure. This means that the better the corporate governance mechanism and the greater the ownership of public shares which is also influenced by the type of industry in the company, the wider CSR disclosure can be made. The results of this study can also theoretically confirm the Stakeholder Theory which plays an important role in the company's sustainability.